2021
DOI: 10.3390/ma14195665
|View full text |Cite
|
Sign up to set email alerts
|

Microbial-Induced Carbonate Precipitation Improves Physical and Structural Properties of Nanjing Ancient City Walls

Abstract: The preservation and restoration of heritage sites have always been of key focus in the field of cultural relics. Current restoration methods mainly involve physical or chemical techniques, which are in many cases intrusive, destructive, and irreversible. Hereby, we introduce a novel biological strategy (microbial-induced carbonate precipitation (MICP)) to repair natural and simulated surface cracks on six hundred years’ old wall bricks (part of the Nanjing City Min Dynasty ancient wall, China). X-ray micro co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The type and concentration of chemicals used in MICP play a crucial role in controlling the calcium and carbon source [22] as well as contribute to the types and amount of precipitation. The most commonly selected chemicals for MICP are urea, which is hydrolyzed to carbonate ions [23], and calcium chloride, as a source of calcium ions reacting with carbonate ions (Table 1). S. pasteurii growth medium (in 0.13 mol/L tris buffer, 10 g/L (NH4)2SO4, 20 MgCl 2 (0, 0.05, 0.1, 0.25, 0.5 M).…”
Section: Introductionmentioning
confidence: 99%
“…The type and concentration of chemicals used in MICP play a crucial role in controlling the calcium and carbon source [22] as well as contribute to the types and amount of precipitation. The most commonly selected chemicals for MICP are urea, which is hydrolyzed to carbonate ions [23], and calcium chloride, as a source of calcium ions reacting with carbonate ions (Table 1). S. pasteurii growth medium (in 0.13 mol/L tris buffer, 10 g/L (NH4)2SO4, 20 MgCl 2 (0, 0.05, 0.1, 0.25, 0.5 M).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the potential of the recycling ability could be affected if non-mineral grout materials were used. Mu et al [4] summarised further advantages and disadvantages of various conventional grouting materials, i.e., they suggested that mortar-based grouts could cause efflorescence of the masonry due to the high alkalinity.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a huge demand for research on proper injection methods which achieve an effective CaCO 3 distribution [8]. Some studies have already focused on possible MICP applications on bricks, stones or masonry [4,[9][10][11][12]. Jimenez-Lopez et al [12] developed biomineralization experiments by activated bacteria inhabiting the stone for consolidation and increasing the resistance to the deterioration of stone pieces.…”
Section: Introductionmentioning
confidence: 99%
“…MICP has been used for many purposes, such as improvement of the physical and mechanical properties of soil [ 3 ], remediation of contaminated soil [ 4 ], repair of concrete cracks [ 5 ], restoration of ancient buildings [ 6 , 7 ], reinforcement of liquefied foundations [ 8 ], suppression of flying dust [ 9 ], prevention of rock and soil seepage [ 10 ], and mitigation of the greenhouse effect [ 11 ]. MICP is a popular research direction in geotechnical engineering, and the strength of sand reinforced by MICP is considerably improved, although shortcomings of brittle failure are observed [ 12 , 13 , 14 , 15 ], leading to the limitation of large-scale promotion and use of the technology.…”
Section: Introductionmentioning
confidence: 99%